ISLAMIZATION OF HUMAN KNOWLEDGE IN INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA: A FEW CONCEPTUAL CLARIFICATIONS - Muhammad Mumtaz Ali (Tunas Harapan Ummat Foundation, 2026)
This paper examines the project of Islamization of Human Knowledge (IOHK), originally conceptualized and articulated by Ismail Raji al-Faruqi in 1982 within the broader context of intellectual reform in the Muslim world. The IOHK framework was later institutionalized as a core mission of the International Islamic University Malaysia (IIUM) in the 1990s, where it underwent further development and contextual adaptation. The study highlights key features and enhancements introduced by successive IIUM rectors, which have significantly broadened the scope, application, and relevance of IOHK in contemporary educational settings. These additions have transformed IOHK from a primarily theoretical construct into a more comprehensive and operational paradigm for integrating Islamic Revealed Knowledge with the modern disciplines of human sciences. Employing a qualitative methodology based on content analysis, the paper critically examines the evolution of IOHK and situates it within its proper academic and intellectual context. It further clarifies several conceptual dimensions, including its epistemological foundations, methodological implications, and educational objectives. The paper argues that IOHK, as developed and practiced at IIUM, represents not only an educational reform agenda but also a vital framework for civilizational renewal. By fostering a balanced synthesis between spiritual values and scientific inquiry, IOHK contributes to the holistic development of knowledge and promotes the well-being of humanity in an increasingly complex and pluralistic world.